The Intestinal Microbiota of Tadpoles Differs from Those of Syntopic Aquatic Invertebrates - Lyra, Mariana L. [UNESP]; Bletz, Molly C.; Haddad, Célio F. B. [UNESP]; Vences, Miguel (My University, 2018)
Bacterial communities associated to eukaryotes play important roles in the physiology, development, and health of their hosts. Here, we examine the intestinal microbiota in tadpoles and aquatic invertebrates (insects and gastropods) to better understand the degree of specialization in the tadpole microbiotas. Samples were collected at the same time in one pond, and the V4 region of the bacterial 16S rRNA gene was sequenced with Illumina amplicon sequencing. We found that bacterial richness and diversity were highest in two studied snail individuals, intermediate in tadpoles, and lowest in the four groups of aquatic insects. All groups had substantial numbers of exclusive bacterial operational taxonomic units (OTUs) in their guts, but also shared a high proportion of OTUs, probably corresponding to transient environmental bacteria. Significant differences were found for all pairwise comparisons of tadpoles and snails with the major groups of insects, but not among insect groups or between snails and tadpoles. The similarity between tadpoles and snails may be related to similar feeding mode as both snails and tadpoles scratch biofilms and algae from surfaces; however, this requires confirmation due to low sample sizes. Overall, the gut microbiota differences found among syntopic aquatic animals are likely shaped by both food preferences and host identity.
Keywords: 16S rRNA; Aquatic invertebrates; Bacterial community; Gut; Illumina sequencing; Tadpoles